Resenhas - Sund, Mikel; Andrade, Juracy; de Freitas, Osman; Furter, Pierre; Costa Lima, Luiz; de Carvalho, Arthur Eduardo; Costa Ferreira, Orlando; Frederico Cortez, Marcius; Pinheiro, Adão (Estudos Universitários)
Resenhas de Mikel Sund, Juracy Andrade, Osman de Freitas, Pierre Furter, Luiz Costa Lima, Arthur Eduardo de Carvalho, Orlando Costa Ferreira, Marcius Frederico Cortez, Adão Pinheiro.